The Impact of the COVID-19 Pandemic on Childhood Obesity and Lifestyle-A Report from Italy - Stefano Palermi; Marco Vecchiato; Sonia Pennella; Anna Marasca; Alessandro Spinelli; Mariarosaria De Luca; Lorena De Martino; Fredrick Fernando; Felice Sirico; Alessandro Biffi (MDPI AG, 2022)
During the COVID-19 lockdown, especially in the first wave of pandemic (March 2020), sedentary lifestyle and calorie intake increase in children became considerably more prevalent. The aim of the present paper was to evaluate changes in children's weights and nutritional habits during the COVID-19 pandemic in Italy. In this cross-sectional observational study, for 3 years, as part of the corporate wellness program (2019-2021) in Emilia Romagna region of Italy, anthropometric data of Ferrari car company employers' children were collected, analyzed, and compared. Moreover, at the visit of November 2020, performed after the first wave of the pandemic with the most rigorous lockdown rules in Italy, a questionnaire on nutritional and lifestyle habits was administered. We evaluated 307 children (163 M, 10.1 ± 2.3 mean aged in 2019). A significant increase in BMI percentile in 2020 (65.2) compared to 2019 (49.2) was observed; it was confirmed, albeit slightly decreased, in 2021 (64.5). About one-third of participants reported an increase in consumption of fatty condiments and more than half report an increase in consumption of junk food. Levels of physical activity were still high during the COVID-19 lockdown, while sleeping time was significantly reduced. Our findings alert us to the importance of carefully monitoring eating behaviors in young to avoid the adoption of unhealthy food habits and prevent childhood obesity, especially during the period of COVID-19 lockdown.